Transcriptional regulation of the Hedgehog effector CI by the zinc-finger gene combgap. - Campbell, G.L.; Tomlinson, A. (Development, 2000)
Members of the Hedgehog (HH) family of secreted signaling molecules specify cell fate during animal development by controlling the activity of members of the Gli family of zinc-finger transcription factors in responding cells. In Drosophila the Gli homolog, cubitus interruptus (CI), is expressed only in the anterior compartment where it represses targets such as the signaling molecule genes decapentaplegic (dpp) and wingless (wg). HH is expressed in the posterior and diffuses into the anterior where it antagonizes CI repression resulting in dpp and wg expression immediately anterior to the compartment border. Reducing CI levels results in misexpression of wg and dpp, while CI misexpression in the posterior disrupts differentiation. Thus, normal disc patterning requires high levels of CI in the anterior and the absence of CI in the posterior. Here we show that mutations in combgap (cg) result in deregulation of CI expression, which is now expressed at much lower levels and ubiquitously, i.e., also in the posterior. Consequently, cg mutants phenocopy ci loss-of-function mutants in the anterior and ci gain-of-function mutants in the posterior. cg encodes a putative DNA-binding protein that regulates both transcriptional activation and repression of the ci gene.